INTERAKSI VULKANIK DAN TEKTONIK DI PULAU SANGIHE DAN GUNUNG AWU: SEBUAH STUDI INTEGRATIF DALAM KONTEKS GEOLOGI INDONESIA - Rachmadhan, H. D.; Djaya, J.H.M. (LPPM Universitas PRISMA, 2023)
This study delves into the geology and geodynamic processes of Sangihe Island and Mount Awu in North Sulawesi, Indonesia, within the Pacific Ring of Fire. Sangihe Island is renowned for its intensive volcanic activity and significant tectonic phenomena. The primary focus of this study is to understand the complex stratigraphy and the interaction between volcanic and tectonic processes that shape the unique geology of this region. Research methods include field observations, petrographic analysis, and data integration to reveal the history and variety of volcanic activities, as well as the diversity of rocks such as tuff, basalt, and andesite that form the island landscape through Plinian eruptions, lava flows, and pyroclastic deposits. Tectonically, Sangihe Island lies in the subduction zone between the Pacific and Eurasian Plates, creating seismic patterns and crustal deformations that are significant. The study also uncovers subsurface structures and fault systems that influence tectonic activities in the region, providing deep insights into the geodynamic processes at play. The implications of this research include geohazard risk mitigation and sustainable natural resource management. This study makes a significant contribution to understanding the geological complexity of the Pacific Ring of Fire, emphasizing the importance of interactions between volcanic and tectonic processes in shaping dynamic and hazardous geological landscapes.